KONTRIBUSI AGROFORESTRI DAN FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN KELOMPOK KEMITRAAN KONSERVASI DI TAHURA WAN ABDUL RACHMAN - Wati, Mira Amelda; Kaskoyo, Hari; Nurindarwati, Rini; Qurniati, Rommy; Puspasari, Eny (JURNAL RIMBA LESTARI, 2022)
Agroforestry is a land management system that can overcome food problems, the application of which is to combine two or more types of plants, both forestry and agricultural crops. The application of agroforestry in Lampung has been implemented, one of which is Pesawaran Sub-village, Pesawaran Village, Kedondong District, Pesawaran Regency, Lampung. The contribution obtained from forest land using an agroforestry system to people's income is the yield of agricultural crops on a weekly, monthly or annual basis, depending on the type of agricultural crops planted. This study aims to determine the contribution of agroforestry to income and the factors that influence farmers' income in Sejahtera 4 Forest Farmers Group (FFG). This study uses interview and observation methods and multiple linear regression to analyze the data. The results show that agroforestry contributes 25.64% of income, or around Rp. 111,306,690 lower than that of non-agroforestry, contributing 74.36% of income or around Rp. 322,800,000. The results of the analysis show that age has a significant effect on farmers' income in FFG of Sejahtera 4. In contrast, plot area, number of plant species, the combination of plant types, and level of education have no significant effect on income.